The notion of Information Science – A Terminological Approach (Filologia e Linguística Portuguesa, 2012)
The comprehension of the identifying characteristics of Information Science is a contemporary necessity observed in the context of postmodernity. The starting point of this study is the terminological analysis of the term Information Science, using the principal procedures for analysis and synthesis in contemporary orientation of the Communicative Theory of Terminology. Analysis of these definitions allows for the main characteristics of the area to be identified, in order to corroborate a better definition of the Information Science field.